Parvovirus replication. - Berns, K I (1990)
The members of the family Parvoviridae are among the smallest of the DNA viruses, with a linear single-stranded genome of about 5 kilobases. Currently the family is divided into three genera, two of which contain viruses of vertebrates and a third containing insect viruses. This review concentrates on the vertebrate viruses, with emphasis on recent advances in our insights into the molecular biology of viral replication. Traditionally the vertebrate viruses have been distinguished by the presence or absence of a requirement for a coinfection with a helper virus before productive infection can occur, hence the notion that the dependoviruses (adeno-associated viruses [AAV]) are defective. Recent data would suggest that not only is there a great deal of structural and genetic organizational similarity between the two types of vertebrate viruses, but also there is significant similarity in the molecular biology of productive replication. What differs is the physiological condition of the host cell that renders it permissive. Healthy dividing cells are permissive for productive replication by autonomous parvoviruses; such cells result in latent infection by dependoviruses. For a cell to become permissive for productive AAV replication, it must have been exposed to toxic conditions which activate a latent AAV genome. Such conditions can be caused by helper-virus infection or exposure to physical (UV light) or chemical (some carcinogens) agents. In this paper the molecular biology of replication is reviewed, with special emphasis on the role of the host and the consequences of viral infection for the host.